Hellhole : awakening - Herbert, Brian (Herbert, Brian. Hellhole series, 2013)
A confrontation between General Adolphus and the fleets of Diadem Michella Duchenet is compromised by a shadow-Xayan mental blast, an imminent asteroid collision in the outer Candela system, and a fanatical band of rogue telemancers.